Profit efficiency of layer production in Ghana - Yevu, Mawuli; Onumah, Edward Ebo (Elsevier, 2021)
This study assesses profit efficiency and its determinants of intensive housing system of layer production in Ghana. A normalized translog stochastic profit frontier model is employed using cross-sectional data of 300 layer producers in nine districts of Brong Ahafo and Greater Accra regions. The results show that the costs of feed and labour are the most significant factors negatively affecting the profit levels of layer producers. All the input variables respond positively to layer output. Layer producers are about 54% profit efficient and characterized by increasing returns to scale. However, training in poultry farming, farmer-based organization membership, provision of extension service, gender, experience, housing type and mortality rate are the key factors that significantly explain the variations in profit efficiency. The study concludes that on average, layer producers are operating with profit gap of about 46%. The implication of the findings is that training of layer producers by extension services (veterinary officers) in early detection of poultry disease and control are key to reducing inefficiency level to achieve higher profits. Membership of associations by layer producers is key to increasing efficiency in poultry production.